SISTEM PAKAR DIAGNOSA PENYAKIT KULIT KUCING DENGAN METODE FORWARD CHAINING - Juang Julian; Herdi Budiman; Gunawan Gunawan; Ferdinand Murni Hamundu; Andi Tenriawaru; Putu Nara Kusuma Prasanjaya (AnoaTIK: Jurnal Teknologi Informasi dan Komputer, 2025)
In this study, an expert system has been developed for diagnosing skin diseases in cats using the forward chaining method. This system is designed to assist cat owners and veterinary health experts in identifying common skin diseases in cats based on observed symptoms. Forward chaining is used as the inference technique, where the system starts from the initial information or symptoms provided by the user and then progresses through relevant rules to reach a conclusion or diagnosis. The system utilizes a knowledge base consisting of various rules and facts about feline skin diseases. Testing results from 15 test data show that the system has an accuracy rate of 93% and an error rate of 7%. This indicates that the system has a high level of accuracy in diagnosing various types of skin diseases in cats and provides appropriate treatment solutions based on the generated diagnosis.